(untitled) (Fiep Bulletin - online, 2015)
One ofthe kid’s most appreciated and outstanding activity is playing. They like to live activities that proportion them to use the freedom of their movements: jumping, running, leap, shout, it means, activities that express liberty and fun. Kids easily find this possibility of motion in games and plays. Investigating the content of tradition games and plays on school physical education classes of Mossoró’s elementary school.The objective was to verify how many teachers include this subject in their classes and what are the difficulties faced to develop this subject. Data sample was done through a semi-structured interview. The answers were transcribed and thenanalyzed using Bardin’s content analysis (1979). The analysis stages were: pre-analysis, exploration of data and results treatment and interpretation. Results suggest that most of the teachers uses traditional games and plays, but they have difficulties in this matter. Also it is used in a limited way and it is meaningless for the student.